Description de quelques procédés linguistiques de l’ironie, par le biais des tweets sur les transports en commun en français et en polonais - Grezka, Aude; Niziołek, Małgorzata; Buscaldi, Davide (Studia Romanica Posnaniensia, 2019)
Irony is a complex phenomenon. Even though the numerous theories of irony differ from one another, they all seem to agree on the fact that irony implies certain contradiction / discrepancy / inconsistency between what is said and the reality. The purpose of this paper is to describe the language criteria of irony. The studies are contrastive character (French and Polish corpora of tweets about public transport). In the first phase of the study based on contrastive linguistic analysis, we will answer the following questions: What are the language criteria of irony? Are they identical for both languages? The research will help to expand the knowledge of automatic processing of natural language and, more precisely, in the analysis of text data and searching in texts.